2019
DOI: 10.18393/ejss.544747
|View full text |Cite
|
Sign up to set email alerts
|

Relative potential of rhizobium species to enhance the growth and yield attributes of cotton (Gossypium hirsutum L.)

Abstract: Legumes compensate mineral fertilizer by fixing nitrogen due to the specialized structures i.e. nodules by Rhizobium species. Literature revealed that legumes fixed nitrogen due to Rhizobium inoculation from 50-300 kg NPK ha-1 year-1. Rhizobium besides nitrogen fixation, solubilized phosphates, produced growth hormones and due to its root colonizing ability improved the growth and yield of non-legumes also and performed as plant growth promoting rhizobacteria (PGPR). Study was conducted to assess the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…To reduce the negative effects of salt stress on the growth and yield of plant a lot of research work has been conducted. Different techniques of biology like seed/plant treatments with plant growth promoting bacteria (PGPR) and exogenous application of growth hormones which make defense under stress conditions are previously studied (Hayat et al, 2010;Ullah et al, 2017;Qureshi et al, 2019). Among plant growth regulators salicylic acid is one of them which play a role in defensive system against different stresses either biotic or abiotic (Szalai et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the negative effects of salt stress on the growth and yield of plant a lot of research work has been conducted. Different techniques of biology like seed/plant treatments with plant growth promoting bacteria (PGPR) and exogenous application of growth hormones which make defense under stress conditions are previously studied (Hayat et al, 2010;Ullah et al, 2017;Qureshi et al, 2019). Among plant growth regulators salicylic acid is one of them which play a role in defensive system against different stresses either biotic or abiotic (Szalai et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, minimum cotton growth and yield improvement occurred in the uninoculated control and without fertilizer. Qureshi et al [51] reported an increase in shoot mass, root mass, shoot length, root length, boll weight, number of bolls, and seed cotton yield by applying Rhizobium isolate Br5.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin synthesising PGPRs have been identified amongst bacterial genera like Agrobacterium, Pantoea, Bacillus, Moraxella, Pseudomonas, Gluconobacter and Micrococcus ( Barazani and Friedman, 1999 ; Liu et al., 2016 ). Inoculation with PGPRs increased IAA production ( Liu et al., 2016 ), root biomass in wheat ( Kudoyarova et al., 2017 ), yield in maize, cotton, canola ( Iqbal et al., 2015 , Iqbal et al., 2023 ; Qureshi et al., 2019 ) as well as certain active components viz essential oils in medicinal and aromatic plants ( Santoro et al., 2011 ; Darzi et al., 2015 ; Santoro et al., 2015 ; Mishra et al., 2017 ). P. fluorescens and Bacillus spp.…”
Section: Phytohormone Productionmentioning
confidence: 99%